PROTAC: An Effective Targeted Protein Degradation Strategy for Cancer Therapy - Qi, Si-Min; Dong, Jinyun; Xu, Zhi-Yuan; Cheng, Xiang-Dong; Zhang, Wei-Dong; Qin, Jiang-Jiang (Frontiers in Pharmacology, 2021)
Proteolysis targeting chimeric (PROTAC) technology is an effective endogenous protein degradation tool developed in recent years that can ubiquitinate the target proteins through the ubiquitin-proteasome system (UPS) to achieve an effect on tumor growth. A number of literature studies on PROTAC technology have proved an insight into the feasibility of PROTAC technology to degrade target proteins. Additionally, the first oral PROTACs (ARV-110 and ARV-471) have shown encouraging results in clinical trials for prostate and breast cancer treatment, which inspires a greater enthusiasm for PROTAC research. Here we focus on the structures and mechanisms of PROTACs and describe several classes of effective PROTAC degraders based on E3 ligases.